The influence of a non-linear lecturing approach on student attention: Implementation and assessment (2015)
This paper presents a change made to the lecturing approach used within a specific course. The new lecturing approach is based on a non-linear structure where each lesson combines concepts from different topics, in contrast to the traditional linear structure in which each topic is treated separately. The objective of the non-linear approach is to increase student dynamism and motivation and to foster teacher-student dialog. Assessments from students who were taught according to the traditional linear structure along with assessments from students who were taught under both the linear and non-linear approaches are presented. Results show that the non-linear lecturing approach was welcomed and led to a higher degree of student dynamism and motivation and to more tea-cher-student dialog.